Analysis of the Damage Level of the Road Pavement Surface with the Surface Distress Index (SDI) Method as a Basis for Road Maintenance - Sudirman Latjemma (Formosa Journal of Sustainable Research, 2023)
Pavement is the main structure of road construction where the pavement management system is required to determine the condition of the road pavement structure. Factors that can affect road pavements are weather, traffic, construction implementation, pavement design, and maintenance. Each layer of pavement has a design life and with increasing pavement design life, the road condition will gradually decrease until it reaches a level that must be repaired. The research was carried out by observing the condition of the damaged road pavement, using the Surface Distress Index (SDI) method, based on the SDM 03/RCS guideline regarding the 2011 road condition survey. In this study, a Surface Distress Index (SDI) value of 5.25 was obtained for Jalan Bilo-Tambun Tolitoli Regency. From the value of road conditions based on the SDI criteria, it was found that the road conditions were in good condition and the recommendation for handling the road was to receive routine maintenance